Crystallization behavior and properties of fluorcanasite–lithium disilicate glasses for potential use in dental application. Issue 17 (1st December 2019) - Abo-Mosallam, H.A.; Mahdy, Ebrahim A.
Abstract: This work describes the preparation, crystallization behavior, and properties of glasses in the fluorcanasite-lithium disilicate system with the objective of understanding the underpinning science for the development of new glass-ceramics with improved chemical and physical properties in order to examine their potential use as restorative dental materials. Fluorcanasite/frankamenite-A and lithium disilicate were the main crystalline phases developed by the controlled crystallization of the prepared glasses. As lithium disilicate is substituted for fluorcanasite for glasses led to improve in the crystallization tendency, this is attributed to the levels of crosslinking in the glasses is reduced. Glass-ceramics produced were tested for chemical stability by immersing in three solutions that is, HCl, acetic acid, and NaOH. Glass-ceramics were observed degrade greater extent in the alkaline solution, while the solubility decreases significantly in acetic acid. The results also clearly show that chemical durability greatly improved with the addition of lithium disilicate instead of flurocanasite. The produced glass-ceramics has a coefficient of thermal expansion ranged between 95x 10 −7 and 120x 10 −7  °C −1 (25–400 °C) temperature range; while the density ranged from 2.442 to 2.603 g/cm 3 .These results show that it is possible to design a new material that is suitable for use as a dental restoration based on flurocanasite and lithium disilicate glass-ceramics.